Effects of a snake venom metalloproteinase, triflamp, on platelet aggregation, platelet-neutrophil and neutrophilneutrophil interactions: involvement of platelet GPIbα. and neutrophil PSGL-1 - Tseng, Yu-Lun; Lee, Chia-Jung; Huang, Tur-Fu (Thrombosis and Haemostasis, 2004)
The biologically active components fromViperidae venoms specifically affect cell-matrix interactions, and have been utilized for developing anti-adhesive therapy as anti-thrombotic and antiangiogenic agents. Utilizing platelet aggregometry coupled with flow cytometry, we found that a metalloproteinase isolated from Trimeresurus flavoviridis, termed triflamp, inhibited heterotypic adhesion between platelets and neutrophils in whole blood samples. Triflamp is a monomeric glycoprotein with a molecular weight of ∼28 kDa. Triflamp has a N-terminal amino acid sequence homologous to other venom metalloproteinases isolated from T. flavoviridis. The enzymatic activity of triflamp was inhibited by EDTA and phenanthroline but not by PMSF. Moreover, triflamp is a pure α-fibrinogenase. Studies aimed at determining the nature of triflamp in affecting platelets or neutrophils revealed a selective inhibitory activity to glycoprotein (GP) Ibα.-dependent platelet aggregation and PSGL-1-dependent neutrophil homotypic aggregation, indicating that its effects are rather specific. As judged by Western blotting, GPIbα. on platelets and PSGL-1 on neutrophils are the substrates of triflamp. In conclusion, we suggest the novel role of venom metalloproteinase from Viperidae affecting the blood cell-cell interactions, thus offering a potential approach for further exploration of anti-inflammatory agents.
Keywords: Triflamp; metalloproteinase; glycoprotein Ibα; PSGL-1; neutrophil-platelet interaction